ELECTRONIC AIR TRAFFIC SERVICE (ATS) ROUTE AS A SUPPORT OF EN-ROUTE FLIGHT INFORMATION (EFI) AND FLIGHT PLAN LEARNING FOR AVIATION SAFETY CADETS AT AVIATION POLYTECHNIC OF SURABAYA - Alhasanah, Safira; Rochmawati, Laila; Akbar Awal Rozaq, Hasri; Aman, Syahrul; Maharani Sukma, Meita (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
ATS Route is a certain route designed to channel the traffic flow required for the provision of air traffic services. ATS Route Electronic Website, a product created to support aviation safety cadets practice on flight routes. The ATS Route Electronic product only displays domestic routes within Indonesia. In this research method used in analysing the writing data of this final project is the quantitative R&D method, a research whose analysis results are presented in the form of numbers which are then explained and interpreted in the form of descriptions. This product has received validation from experts and respondents from the research sample. As well as getting product trial results with a good value index. The results of the calculation of 92% state that the website product is suitable for use, while 8% there are still deficiencies that can be developed again